Roles of Histone Deacetylases in Acute Myeloid Leukemia With Fusion Proteins - Zhang, Juan; Gao, Xuefeng; Yu, Li (Frontiers in Oncology, 2021)
Accurate orchestration of gene expression is critical for the process of normal hematopoiesis, and dysregulation is closely associated with leukemogenesis. Epigenetic aberration is one of the major causes contributing to acute myeloid leukemia (AML), where chromosomal rearrangements are frequently found. Increasing evidences have shown the pivotal roles of histone deacetylases (HDACs) in chromatin remodeling, which are involved in stemness maintenance, cell fate determination, proliferation and differentiation, via mastering the transcriptional switch of key genes. In abnormal, these functions can be bloomed to elicit carcinogenesis. Presently, HDAC family members are appealing targets for drug exploration, many of which have been deployed to the AML treatment. As the majority of AML events are associated with chromosomal translocation resulting in oncogenic fusion proteins, it is valuable to comprehensively understand the mutual interactions between HDACs and oncogenic proteins. Therefore, we reviewed the process of leukemogenesis and roles of HDAC members acting in this progress, providing an insight for the target anchoring, investigation of hyperacetylated-agents, and how the current knowledge could be applied in AML treatment.